THE NON-OBSERVANCE OF MAXIMS IN DIALOGUES OF HARRY POTTER AND THE CURSED CHILD BOOK - Zahra, Tsabitah Nadifah; Suyudi, Ichwan (Journal of Language and Literature, 2023)
This research focuses on the non-observance of Grice’s maxims which is identified by the characters’ dialogues. The well-known Harry Potter series book is chosen as the source of the data for researcher to find the pragmatic aspect, which is not usually clearly shown. The research aims to find the non-observance of maxims and find the most frequent non-observance of maxims that the characters perform by using descriptive qualitative method. The result of the data analysis were 20 data of flouting maxim of quantity, 4 data of flouting maxim of quality, 28 data of flouting maxim relation, 12 data of flouting maxim manner, 5 data of violating maxim of quantity, 10 data of violating maxim of quality, 44 data of violating maxim of relation, 27 data of violating maxim of manner, 2 data of infringing of maxims, 1 data for Opting-out of maxims and 0 data of Suspending of maxims. Based on the number of data found, the most frequent non-observance performed was violating maxim of relation